The Identities of Catherine de' Medici - Broomhall, Susan, author.
1 online resource.
Keywords: In The Identities of Catherine de' Medici , Susan Broomhall provides an innovative analysis of the representational strategies that constructed Catherine de' Medici and sought to explain her behaviour and motivations. Through her detailed exploration of the identities that the queen, her allies, supporters, and clients sought to project, and how contemporaries responded to them, Broomhall establishes a new vision of this important sixteenth-century protagonist, a clearer understanding of the dialogic and dynamic nature of identity construction and reception, and its consequences for Catherine de' Medici's legacy, memory, and historiography.